Reading the textual thresholds of Adonis' book '' Beginnings of the Body, Ends of the Sea " - حامد جابر, يوسف; مخلوف , نور فيصل (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The text is a construct that cannot reach its various spaces without standing at its thresholds, as there is no naked text and it must be covered with a title, which is the entrance that precedes the body of the text, its significance is complete only with it. Standing at the thresholds allows the reader to stand at the writer's thoughts and reveal the relationship of the title to the content as it is the interpretive key to open the text lockers, and because it falls within the system of parallel thresholds, it is not inside or outside the text, but in the case of a relationship with it. Hence this approach came to emphasize the importance of these thresholds in reading poetic texts as they are conditional and necessary input, it is necessary to build an initial vision to understand the text. Especially that this study is concerned with Adonis in his poetry collection, " Beginnings of the Body, Ends of the Sea ", Adonis's thresholds are rich and open to endless readings. Adonis, a poet who excels in choosing his thresholds is overwhelmed by poetry, as if you were standing in front of a small, intense poetic passage, foreshadowing the greater explosion of the text universes and their implications.